An achievement test in fourth year high school English - Carag, Teresa A. 1928- (publisher not identified], 1964)
This study presents the procedures and problems in the construction of an achievement test. The construction includes: (1) the experimental run, (2) the item analysis, (3) the item revision, and (4) the final form of the test.